Overcoming optical losses in thin metal-based recombination layers for efficient n-i-p perovskite-organic tandem solar cells - Tian, Jingjing; Liu, Chao; Forberich, Karen; Barabash, Anastasia; Xie, Zhiqiang; Qiu, Shudi; Byun, Jiwon; Peng, Zijian; Zhang, Kaicheng; Du, Tian; Sathasivam, Sanjayan; Macdonald, Thomas J.; et al. (Nature Communications, 2025)
Perovskite-organic tandem solar cells (P-O-TSCs) hold substantial potential to surpass the theoretical efficiency limits of single-junction solar cells. However, their performance is hampered by non-ideal interconnection layers (ICLs). Especially in n-i-p configurations, the incorporation of metal nanoparticles negatively introduces serious parasitic absorption, which alleviates photon utilization in organic rear cell and decisively constrains the maximum photocurrent matching with front cell. Here, we demonstrate an efficient strategy to mitigate optical losses in Au-embedded ICLs by tailoring the shape and size distribution of Au nanoparticles via manipulating the underlying surface property. Achieving fewer, smaller, and more uniformly spherical Au nanoparticles significantly minimizes localized surface plasmon resonance absorption, while maintaining efficient electron-hole recombination within ICLs. Consequently, optimized P-O-TSCs combining CsPbI2Br with various organic cells benefit from a substantial current gain of >1.5 mA/cm2 in organic rear cells, achieving a champion efficiency of 25.34%. Meanwhile, optimized ICLs contribute to improved long-term device stability.
CRIS-Team Scopus Importer:2025-01-31